Identification of Social Capital Bonding Inter Trader and Bank Thithil (Study Case in Blimbing Traditional Market, Malang City) - Bunga Hidayati; Agus Suman; Asfi Manzilati (Institute of Research and Community Service, University of Brawijaya)
In traditional market activity, economic actors who are in it not only traders or buyers. But there are also other economic actors who became part of the traders capital resources is loan shark. In terms of Java, loan shark referred to as